La mecánica realista frente al descubrimiento romántico en "España" (1873) de Edmundo de Amicis - López Quintáns, Javier (Dicenda. Estudios de lengua y literatura españolas, 2013)
Many Italian travelers arrived to Spain. Edmundo de Amicis is an unique example, which begins in Turin to discover the peninsula. At this time, an Italian, Amadeo of Savoy, took the Spanish throne. It analyzes the places Amicis visits: Zaragoza and the monastery of Montserrat, the Coso, the Basílica del Pilar, the Torre Nueva; with Burgos, the Cathedral, the monument of the Cid, the main square; Valladolid, the cathedral, the museum paint; the Puerta del Sol in Madrid, the Prado Museum or the armory, or the nearby monastery of the Escorial; the Alcázar and Santa María la Blanca in Toledo; the Alcazar in Seville and the Columbian Library. The paper examines the sources of Amicis´ romantic text (Novalis, Schiller), realistic procedures and the importance of art in the text. It also points the concomitants of this work to that of the most important nineteenth-century Italian travelers.
Keywords: Amicis; travel; Romanticism; Realism